2017
DOI: 10.1126/scitranslmed.aal1669
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic calcification in pseudoxanthoma elasticum responds to inhibition of tissue-nonspecific alkaline phosphatase

Abstract: The ABCs of PXE Pseudoxanthoma elasticum (PXE) is a genetic disorder caused by mutations in ABCC6 that is characterized by calcium deposition outside of the skeletal system, specifically in the blood vessels, skin, and eyes. Using patient-derived fibroblasts and genetic knockout mouse models, Ziegler et al. demonstrate that ABCC6 mutant cells are osteogenic and that loss of ABCC6 reduces pyrophosphate, an inhibitor of calcification. In mice, ectopic calcification was seen only when ABCC6 was deleted jointly fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 51 publications
5
100
0
Order By: Relevance
“…Further studies might require higher doses for more drastic reduction in TNAP activity and complete mineralization arrest. Please note that the investigational drug, the dose at 75 mg/ kg/day, and the Abcc6 e/e mouse model for PXE in this study mirrors those used in another study (Ziegler et al, 2017). Combined results of these independent and complementary studies suggested that inhibition of TNAP by SBI-425 could be turned into a viable approach for treatment of patients with PXE.…”
Section: Q LI Et Almentioning
confidence: 62%
“…Further studies might require higher doses for more drastic reduction in TNAP activity and complete mineralization arrest. Please note that the investigational drug, the dose at 75 mg/ kg/day, and the Abcc6 e/e mouse model for PXE in this study mirrors those used in another study (Ziegler et al, 2017). Combined results of these independent and complementary studies suggested that inhibition of TNAP by SBI-425 could be turned into a viable approach for treatment of patients with PXE.…”
Section: Q LI Et Almentioning
confidence: 62%
“…Its documented expression in chondrocytes and tibia may, however, suggest ABCC6 to be also relevant in human osteoblasts (Beck et al, 2005;Kolesnikov et al, 2015). As such, our knockout model will also be valuable for elucidation of the complex pathomechanisms underlying PXE, the osteogenic changes in particular, as studies suggest that the aberrant inorganic pyrophosphate release that was identified is not the only mechanism leading to ectopic mineralization in PXE (Zhao et al, 2017;Ziegler et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…While studies of single gene knockouts affecting PPi metabolism showed ectopic mineralization of the AF and adjacent ligaments (Warraich et al, 2013; Zhang et al, 2016) LG/J mice recapitulated age‐dependent disc calcification that affected both the NP and AF similar to elderly humans (Chanchairujira et al, 2007). Studies have also shown a causal relationship between systemic activity of TNAP that degrades PPi into Pi and ectopic calcification of soft tissues (Ziegler et al, 2017). Interestingly, blood analysis showed that several mineral metabolism markers including free Ca 2+ and phosphorous were not affected by the strain background.…”
Section: Discussionmentioning
confidence: 99%